On caring and sharing–Addressing psychological, biographical, and spiritual aspects in integrative cancer care: A qualitative interview study on physicians' perspectives. (October 2018) - Kienle, Gunver S.; Mussler, Milena; Fuchs, Dieter; Kiene, Helmut
Abstract: Background: Patients confronted with a cancer diagnosis experience a variety of existential needs encompassing emotional, psychological, and spiritual areas of being. A patient-centered care approach addressing such existential issues is recognized as an essential aspect of health care. The aim of this study is to explore what role psychological, biographical, and spiritual factors play for experienced doctors working in integrative cancer care. Method: The qualitative study was based on in-depth interviews with 35 purposively sampled doctors, all practicing integrative oncology in the field of anthroposophic medicine in hospitals and/or office-based practices in Germany and other countries. Data were analyzed using structured content analysis. Results: Psychological, biographical, and spiritual factors are important issues in integrative cancer care. Prevailing themes identified in this study were enabling patients to participate in life, promoting autonomy and coping, stabilizing patients emotionally and cognitively, overcoming the disease, and–primarily if addressed by patients–integrating spiritual issues. Doctors offered conversation, counseling, and time, but also referred to art, music, literature, and nature, so that patients' ongoing emotional, psychological, and spiritual needs could be explored and addressed. Doctors' attitudes with regard to existential issues were seen as important, as was maintaining an attitude of openness towards existential issues. Conclusion: Doctors in integrative cancer care utilize different methods to explore the needs of patients and employ a variety of treatment methods that address not just patients' medical issues but their existential concerns as well.